Culture of sustainability in higher education. The case of the Popular University of Chontalpa in Tabasco, Mexico (Revista de Investigaciones Universidad del Quindío, 2022)
Universities are facing the challenge of including in an assertive way the paradigm of sustainability into their philosophy and getting to transcend throughout the community in order to contribute to human development. The promotion of an institutional culture based on sustainability implies the commitment and leadership of directors, teachers and students in order to undertake actions to face problems caused by the environmental crisis. In this sense, a case study of UPCH students is presented. The objective was to analyze the perception of university management in raising awareness of environmental issues and in the formation of a culture with a sustainable vision. The research has a quantitative, descriptive and transactional approach, 497 participants were surveyed in order to analyze four categories: appropriation of knowledge, university relationship, university education and socioeconomic impact. The results confirm the hypothesis that the majority of the student community lacks of enough information about the achievements of the university and that the actions carried out to promote a sustainable culture are not fully perceived.
Keywords: sustainability; university; institutional culture and environmental education